Microbial Etiology and Antibiotic Sensitivity Patterns of Urinary Tract Infections in a Tertiary Care Hospital - Ullah, Sadeed; Khan, Illeeyeen; Gul, Warda; Gul, Sabawoon; Zeeshan, Zeeshan; Ismail, Ismail; Khan, Hamza (Journal of Neonatal Surgery, 2025)
Background: Urinary tract infections (UTIs) are a significant health concern worldwide, with varying microbial etiology and antibiotic sensitivity patterns. This study is designed to determine the microbial etiology and antibiotic sensitivity patterns of UTIs in a tertiary care hospital. Methods: A descriptive cross-sectional study was conducted in the Department of Urology at Lady Reading Hospital in Peshawar. A total of 100 patients with signs and symptoms of UTIs were selected using purposive consecutive sampling. Urine cultures and antibiotic sensitivity testing were performed to identify the causative organisms and their sensitivity patterns. Results: E. coli was the most common microorganism isolated from urine cultures, accounting for 49.4% of the cases. Klebsiella pneumoniae and Pseudomonas aeruginosa were the second and third most common organisms, respectively. E. coli showed highest sensitivity to fosfomycin (79.1%), nitrofurantoin (74.4%), and amikacin (69.8%). High resistance was observed to fluoroquinolones (ciprofloxacin and levofloxacin), beta-lactams (co-amoxiclav), and third-generation cephalosporins (cefotaxime and ceftriaxone). Conclusion: The study highlights the importance of knowing the local microbiological profile and antibiotic sensitivity patterns in the management of UTIs. The findings suggest that fosfomycin, nitrofurantoin, and amikacin are effective antibiotics for the treatment of UTIs, while fluoroquinolones and cephalosporins may not be effective due to high resistance.